ANALYSIS THE BALANCE IN THE MARCH OF BLIND PEOPLE - Manoel Osmar Seabra Junior; Loiane Maria Zengo; Ana Claudia de Souza Fortaleza; Camila Buonani da Silva; Ismael Forte Freitas; Lonise Caroline Zengo (Revista Gestão & Saúde, 2013)
This paper aims to analyze the balance in gait of blind people and identify if physical activities contributes to the performance of this capacity. The sample was composed by three blind people with an average age of 18 years. Baropodometry was used to assess the stability of the subjects, and then analyzed by using the software Footwork Pro. In order to compare results, it was 47 women participated of it, who were apparently healthy and whose results in the assessment were within the normal range. Some variables used in gait, for lower members, right and left, were analyzed. After the assessment, the analysis was used for comparison of results, T-test for nonparametric independent samples, the results showed an expressive difference in blind subjects, in relation to the stability of the left side. When searching the literature for activities that could be conducted with blind people in order to improve their balance in gait, it was concluded that not all physical activities are effective. Thus, it is extremely important that the professional knows to choose and conduct each activity that stimulates for a better performance.